Kompetensi pedagogik pendidik pada penilaian kognitif dengan platform pembelajaran Kahoot di Masa Covid 19 - Sri Rejeki Murwati; Imam Sutomo (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
This study aims to determine the pedagogic competence of fifth grade teachers at the elementary school level and to find out how teachers carry out cognitive assessments using the Kahoot learning platform. The type of research used is field research or field research. The research method uses descriptive qualitative methods. The subjects of this study were fifth grade teachers at SD Negeri Margorejo Pati District, namely 3 people from three elementary schools in Margorejo Pati District. Sources of data used from interviews, observation and documentation. The data analysis technique uses the Miles and Huberman model, namely data reduction, presenting data with brief descriptions as well as drawing conclusions and verification. The results of the study showed that (1) the competency and performance of the fifth grade PAI teacher at SD Negeri Margorejo Pati District could have pedagogic competency standards according to the Regulation of the Minister of National Education of the Republic of Indonesia No. 16 of 2007 concerning teacher competence (2) learning at SD Negeri Margorejo Pati District was still implemented during the Covid 19 pandemic using the Kahoot platform as an alternative to learning at school. (3) The Kahoot platform further guarantees the effectiveness and efficiency of assessments for teachers in cognitive assessment during the Covid 19 pandemic